Criterios de migración para una red de acceso en el contexto de redes de nueva generación (2006)
This project, at its initial stage, carries out a study and an analysis of the access networks of fixed-telephony operators in Colombia in order to give a further diagnosis of their network state and also implement a general access network model that gathers the common characteristics of operators. Afterward, a general description will be done about architecture, features, advantages, disadvantages and access network services NGN. Later on, a migration model is presented for the access network proposed by the ITU and some migration criteria are determined. These criteria will be used as a reference to the operators in their evolving process toward NGN. At last, a transition process is performed for the general model of access network using the solution of a technological provider and a service model is also performed according to the characteristics of the next generation networks.